2022
DOI: 10.21203/rs.3.rs-2326354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiome-Derived Cobalamin and Succinyl-CoA are Powerful Biomarkers for Improved Screening of Anal Cancer

Abstract: Background. People with HIV (PWH) exhibit a markedly increased risk of anal cancer, especially men who have sex with men (MSM), with specific microbiota signatures possibly contributing to greater human papillomavirus (HPV) oncogenic potential. Low specificity of the current screening strategy for detecting high-grade squamous intraepithelial lesions (HSIL) hinders anal cancer prevention. We investigated microbiome derivatives associated with HSIL in anal cytology samples. Methods. We recruited a discovery a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 61 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…We discovered that cobalamin and succinyl-CoA were increased in the anal microbiome of patients with anal precancer and overperformed the reference test—anal cytology—. Furthermore, we validated the findings in an external validation cohort, and we demonstrated greater in vitro production of succinyl-CoA and cobalamin in bacteria associated with HSIL or cancer vs. those presumably protective ( 172 ). Therefore, starting from a clinical question and integrating data from different omic levels we were able to define a new microbiome-based tool that could help in the prevention of a common cancer in PLWH by discovering two powerful biomarkers of anal precancer that could improve anal cancer prevention.…”
Section: Potential and Limitations Of Current Approaches For Understa...mentioning
confidence: 83%
“…We discovered that cobalamin and succinyl-CoA were increased in the anal microbiome of patients with anal precancer and overperformed the reference test—anal cytology—. Furthermore, we validated the findings in an external validation cohort, and we demonstrated greater in vitro production of succinyl-CoA and cobalamin in bacteria associated with HSIL or cancer vs. those presumably protective ( 172 ). Therefore, starting from a clinical question and integrating data from different omic levels we were able to define a new microbiome-based tool that could help in the prevention of a common cancer in PLWH by discovering two powerful biomarkers of anal precancer that could improve anal cancer prevention.…”
Section: Potential and Limitations Of Current Approaches For Understa...mentioning
confidence: 83%
“…A study by Su Shen et al [25] identified an increased abundance of Atopobium and Sneathia linked to cervical lesions, along with several metabolites and metabolic pathways, including taurine, guanine, and uric acid, suggesting high consumption of amino acids, purines, sugars, and esters in the cervicovaginal microenvironment associated with HR-HPV infection and HSIL. A recent investigation of the microbiome functions linked with HSIL, analyzing the composition, proteins, and metabolites derived from the anal microbiome in two cohorts including 213 MSM with HIV, did not find bacterial taxa robustly associated with HSIL, but higher levels of microbiome-encoded proteins producing succinyl coenzyme A and cobalamin were significantly associated with HSIL, thereby improving diagnostic accuracy [26 ▪▪ ].…”
Section: Links Between the Microbiome Composition And Functions And A...mentioning
confidence: 97%
“…Various bacterial biomarkers and derived metabolic pathways have demonstrated high discriminative ability, often outperforming the low specificity of anal cytology. Specifically, cobalamin and succinyl-CoA microbiome-derived metabolites measured in anal cytobrushes have been validated as HSIL biomarkers in parallel cohorts [26 ▪▪ ]. However, there are several limitations to the applicability of these results, such as the need for prospective validation in larger, diverse populations due to factors like interindividual and ethnic microbiome diversity, country of origin, diet, BMI, and coinfections.…”
Section: Links Between the Microbiome Composition And Functions And A...mentioning
confidence: 99%
See 2 more Smart Citations